Should responsibility be used as a tiebreaker in allocation of deceased donor organs for patients suffering from alcohol-related end-stage liver disease? - Hu, Diehua; Primc, Nadia (Medicine, health care and philosophy, 2023)
There is a long-standing debate concerning the eligibility of patients suffering from alcohol-related end-stage liver disease (ARESLD) for deceased donor liver transplantation. The question of retrospective and/or prospective responsibility has been at the center of the ethical discussion. Several authors argue that these patients should at least be regarded as partly responsible for their ARESLD. At the same time, the arguments for retrospective and/or prospective responsibility have been strongly criticized, such that no consensus has been reached. A third option was proposed as a form of compromise, namely that responsibility should only be used as a tiebreaker in liver allocation. The present study provides an ethical investigation of this third option. First, we will provide an overview of the main arguments that have been offered for and against the use of responsibility as an allocation criterion. Second, we will explore the concept of responsibility as a tiebreaker in detail and discuss several types of situations, in which responsibility could be used as a tiebreaker, as well as the main ethical challenges associated with them. As we will show, an ethical justified use of responsibility as a tiebreaker is limited to a very restricted number of cases and is associated with a number of ethical concerns. For this reason, waiting time should be preferred as a tiebreaker in liver allocation, even though the criterion of waiting time, too, raises a number of equity-related concerns.